دور وسائل الإعلام في تعزيز الوعي البيئي لدى طلاب المعهد العالي للعلوم التقنية زوارة (Al-Farooq Journal of Sciences, 2026)
This research aims to investigate the role of specialized environmental media in monitoring environmental issues and developing environmental awareness among students of the Higher Institute of Sciences and Technology in Zuwara. This study is set against the backdrop of increasing environmental challenges facing the Arab region and the urgent need for academic institutions to activate environmental culture. The researcher employed a descriptive-analytical methodology based on the survey method, collecting field data through a specifically designed questionnaire. The data was statistically analyzed using the SPSS software, utilizing frequencies, percentages, weighted means, and T-tests. The study was applied to a sample of students from the Higher Institute of Sciences and Technology in Zuwara to ensure a representative view of the younger, technical generation toward the issues at hand.The research reached several pivotal results, most notably the existence of statistically significant differences in students' opinions regarding the monitoring of environmental issues, indicating a variation in interest based on media sources and presentation methods. The results also proved the effectiveness of diverse journalistic arts in attracting students' attention, emphasizing that the role of media in raising environmental awareness remains varying in its intensity among individuals. The study revealed that the level of satisfaction with the current media treatment of environmental issues is still average, necessitating the development of communication tools to simplify environmental concepts and make them more comprehensible and engaging.The research recommended the necessity of intensifying environmental coverage directed at youth using simplified and attractive presentation methods, and enhancing the use of analytical journalistic arts as a tool for deepening understanding. Furthermore, the recommendations emphasized the importance of developing media content to be more comprehensive and accurate, alongside the necessity of activating cooperation between educational institutions and specialized environmental agencies to produce media material that contributes to consolidating positive environmental behavior and transforming awareness into actual practice within the higher education environment.